Trends in research on acute lung injury/acute respiratory distress syndrome associated with viral pneumonia from 1992 to 2022: a 31-year bibliometric analysis - Zhang, Luofei; Mei, Shenghui; Zhu, Bin; Zhao, Zhigang (Frontiers in Medicine, 2023)
Purpose: Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is a dangerous symptom in patients with severe viral pneumonia. This study aims to comprehensively review the cooperation and influence of countries, institutions, authors and co-cited journals/authors/references and keywords in the field of ALI/ARDS associated with viral pneumonia from the perspective of bibliometrics, evaluate the clustering evolution of knowledge structure, and find hot trends and emerging topics. Methods: Publications on ALI/ARDS associated with viral pneumonia published from January 1, 1992 to December 31, 2022 were extracted from the Web of Science core collection. The document type was limited to original article or review, with the language set to English. Citespace was used to conduct the bibliometric analysis. Results: A total of 929 articles were included, and the number of them generally increased over time. The countries with the most published articles in this field are the United States (320 papers) and Fudan University is the institution (15 papers) with the most research results. The New England Journal of Medicine was the most frequently co-cited journal, while the most influential co-cited journal was American Journal of Clinical Pathology. Reinout A Bem and Cao Bin were the most prolific author, but there was no leader in this field. The keywords with both high frequency and high centrality were ‘pneumonia’, (Freq=169, Central=0.15), ‘infection’ (.Freq=133, Central=0.15), ‘acute lung injury’ (Freq=112, Central=0.18), ‘respiratory distress syndrome’ (Freq=108, Central=0.24), and ‘disease’ (Freq=61, Central=0.17). ‘Failure’ was the first keyword with citation bursts. Meanwhile, ‘coronavirus’, ‘cytokine storm’ and ‘respiratory syndrome coronavirus’ continue to burst. Conclusions: Although there was a surge in literature since 2020, attentions to ALI/ARDS associated with viral pneumonia were still insufficient over last three decades. The communication and cooperation among countries, institutions and authors need to be further strengthened.